2011
DOI: 10.4066/amj.2011.576
|View full text |Cite
|
Sign up to set email alerts
|

Sickness Absenteeism, Morbidity and Workplace Injuries among Iron and Steel workers – A Cross Sectional Study from Karnataka, Southern India

Abstract: Sickness absenteeism is significantly higher among iron and steel workers when compared to other occupations in India. Blue collar workers and shift workers loose higher number of days due to sickness absence, and they face problems related to musculoskeletal system, gastrointestinal system and hypertension in higher proportions compared to their counterparts. Women experienced hypertension as the common health problem and higher proportions of injuries outside the work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 7 publications
4
24
0
Order By: Relevance
“…In other studies, prevalence of overall morbidity was varying from 16 to 81%. [ 4 13 14 ] This might be due to different working conditions, different health facilities, assessment methods, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, prevalence of overall morbidity was varying from 16 to 81%. [ 4 13 14 ] This might be due to different working conditions, different health facilities, assessment methods, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Whereas study by Manjunatha et al ., (2011) on 353 iron and steel workers in Karnataka, South India showed hypertension in 24.4%. [ 4 ] Narlawar et al ., in their cross-sectional study found that prevalence of hypertension among continuous exposure group (25.51%) was significantly higher than intermittent exposure group (14.05%; χ 2 = 14.28, degrees of freedom (df) =1, P < 0.001). [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it is stated that workers engaging higher physical workloads report a higher prevalence of symptoms and in more body regions than those with lighter workloads (Widanarko et al, 2011). Furthermore, the high prevalence of musculoskeletal disorders in blue-collar workers is a major cause of absenteeism, diminished working abilities, higher medical costs and decreased productivity (Hanebuth, Meinel, & Fischer, 2006;Manjunatha, Kiran, & Thankappan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Iron and steel production workers carry out a number of tasks (e.g., iron making, steelmaking, and steel rolling) in iron and steel industries consisting of oven and furnaces, and thus highly exposed to many toxic substances such as metals (e.g., chromium, manganese, lead, and cadmium), carbon monoxide, various dusts, fumes, acid mists, solvents, oil mists, and physical hazards including heat, noise, ionizing radiation and vibration [ 9 ]. Therefore, iron and steel workers are highly associated with many health ailments related to the musculoskeletal system, gastrointestinal system, and respiratory system [ 10 , 11 ]. In addition, it has been reported that the hypertension prevalence rate is strikingly high in Chinese iron and steel workers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%